The Impact of Marketing Mix "5p’s" on the Intention to Purchase a Home Loan in Algerian Banks - Chenni, Talia; Reguig, Mohamed Khalifa (جامعة زيان عاشور بالجلفة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2024)
This study aimed to investigate the factors within the marketing mix that affect purchase intention by examining the marketing practices of Algerian banks. The study focused on the 5Ps of the marketing mix: product, price, place, people, and process. Descriptive and analytical research methods were employed, utilizing both primary data from interviews and questionnaires distributed to 200 bank clients in Algeria and secondary data from various sources, including research papers, books, reports, journals, articles, and relevant websites. Descriptive statistics revealed that respondents acknowledged the impact of the product and place on their intention to purchase a home loan. However, they were less inclined to affirm the influence of price, people, and the transaction process on their purchase intention for housing loans in the bank. The analysis underscores the importance of product quality and location as influential factors on consumer purchase intention. The study suggests that the bank should prioritize maintaining product quality, as consumers appear to prioritize quality over price. Additionally, the bank should strategically expand its presence in areas aligned with customer needs, enhancing communication infrastructure to cater to customer convenience.
Keywords: البنوك الجزائرية -- القروض السكنية -- المزيج التسويقي